RESIDENTS PERCEPTION AND RESPONSE TO URBAN ENVIRONMENTAL PROBLEMS IN JIMETA, YOLA NORTH LACAL GOVERNMENT, ADAMAWA STATE NIGERIA - Yohanna. L; Ezra A; Sini. E. D; Musa. I (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2018)
This study investigates environmental problems in Jimeta Yola North Local Government area. The study made use of both primary and secondary data. The primary data came from responses to interview schedule in which 368 respondents were randomly selected for the study. The secondary data were extracted from both published and unpublished materials especially document from population commission and primary health care numbering in Jimeta Yola North Local Government Adamawa State. The study showed that over 50% of the respondents were of the opinion that flooding and erosion are the most prominent environmental problems in the study area, while less than 40% of the respondents were of the opinion that deforestation and pollution are the prominent environmental problem in the study area. The study also shows management strategy that can be adopted in the area. Over 60% of the respondents were of the opinion that proper drainage and incineration are the best management strategy that can be adopted to manage the environmental problems in the area, while less than 40% of the respondents were of the opinion that other forms of management strategy such as construction of good roads and maintenance of the existing infrastructure can be adopted to manage the environmental problems in the study area. Other health problem prevalent in the study area includes asthma, cholera, malaria and meningitis. Based on the findings of the research, the following recommendations are put forward: Government should encourage and support inhabitants in managing and controlling their environment for health and preserved future environment. Government should look at the environmental problems and organize programmers‘ that would bring about enlightenment to inhabitants and to suggest and implement strategies that will curtail the rate at which environmental hazards are degrading and polluting the environment which leads to havoc at various scales. K